2012
DOI: 10.1215/00127094-1548443
|View full text |Cite
|
Sign up to set email alerts
|

Lattice point asymptotics and volume growth on Teichmüller space

Abstract: We apply some of the ideas of the Ph.D. Thesis of G. A. Margulis [Mar70] to Teichmüller space. Let X be a point in Teichmüller space, and let BR(X) be the ball of radius R centered at X (with distances measured in the Teichmüller metric). We obtain asymptotic formulas as R tends to infinity for the volume of BR(X), and also for the cardinality of the intersection of BR(X) with an orbit of the mapping class group.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
85
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(89 citation statements)
references
References 24 publications
4
85
0
Order By: Relevance
“…This result implies Theorem 1.2. Then we use the basic properties of the Hodge norm [5] to prove a closing lemma for the Teichmüller geodesic flow in §6. But the Hodge norm behaves badly near smaller strata, i.e., near points with degenerating zeros of the quadratic differential.…”
Section: Remarksmentioning
confidence: 99%
“…This result implies Theorem 1.2. Then we use the basic properties of the Hodge norm [5] to prove a closing lemma for the Teichmüller geodesic flow in §6. But the Hodge norm behaves badly near smaller strata, i.e., near points with degenerating zeros of the quadratic differential.…”
Section: Remarksmentioning
confidence: 99%
“…Though enormous hyperbolic characteristics have been observed in Teichmüller space, we would like to notice a remarkable fact proven by Athreya, Bufetov, Eskin and Mirzakhani in [1]. Indeed, they observed that the volume of the metric balls in Teichmüller space has exponential growth.…”
Section: Corollary 12 (Criterion For Parallelism)mentioning
confidence: 77%
“…The author would like to express his hearty gratitude to Professor Ken'ichi Ohshika for fruitful discussions and his constant encouragements. He also thanks Professor Yair Minsky for informing him about a work by Athreya, Bufetov, Eskin and Mirzakhani in [1]. The author also thanks Professor Athanase Papadopoulos for his kindness and useful comments.…”
Section: Corollary 12 (Criterion For Parallelism)mentioning
confidence: 94%
“…By either [Fay73,Yam80] or [ABEM12,§3], there exists N sufficiently large such 14 D. Aulicino that the derivative of the period matrix (X n , ω n ) ∈ M has a 2 × 2 minor of full rank as well. This contradicts the fact that M has maximal Forni subspace and shows that every boundary translation surface is connected.…”
Section: Definition a Multicomponent Translation Surface Is A Collecmentioning
confidence: 99%